Discriminative spatial localisation in confocal reflectance and carbon dots-based fluorescence imaging using mixed-mode endoscopic scanner - Leong Y.S.; Mokhtar M.H.H.; Ahmad Nazri N.A.; Abu Bakar M.H.; Zan M.S.D.; Arsad N.; Abdul P.M.; A. Bakar A.A. (Taylor and Francis Ltd., 2025)
Carbon dots (CDs)-based fluorescence imaging with confocal reflectance effectively localises labelled structures with clear sample visualization. Yet, integrating these modalities into single-fibre cantilever-based endoscopic scanners poses challenges. Thus, we present an endoscopic scanner with a mixed-mode fibre cantilever for dual modalities imaging. The cantilever features two-attached fibre construction for multiple illumination and detection channels without additional optical components. The measured lateral and axial resolutions are 5.81 and 6.52 m, respectively with field-of-view of 408 ? 488 m. The fluorescence detection capability was first verified using fluorescent microspheres and CD-embedded polymer film, followed by confocal reflectance and CDs-based fluorescence imaging on labelled fibrous network and plant samples. The results demonstrate the complementary strengths of confocal reflectance, which extracts surface profiles, and CDs-based fluorescence, which captures fluorescence signals, leading to precise localization of fluorescence signals within the sample. Switching modality schemes at the scanner?s back-end enables implementation of different modalities. ? 2024 The Author(s). Published with license by Taylor & Francis Group, LLC.